Controlled chain reaction as a regulatory technique - Bodo, Peter (International Advances in Economic Research, 1996)
This paper discusses a regulatory technique that consists of the use of a controlled chain reaction to influence social and economic processes. It claims that this method was employed by Hungarian control agencies to further centralize the farm sector in the 1970s. Section I of the paper presents three versions of this technique. Section II shows how the institutional structure of Hungarian agriculture made the application of this technique possible. (JEL P21).
Keywords: dept.eco; dept.fin